Welcome to Westonci.ca, the Q&A platform where your questions are met with detailed answers from experienced experts. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

hey can you help me answer this question by giving me the answer?

Hey Can You Help Me Answer This Question By Giving Me The Answer class=

Sagot :

The value of f(a)=4-2a+6[tex]a^{2}[/tex], f(a+h) is [tex]6a^{2} +6h^{2} -2a-2h+12ah[/tex] , [f(a+h)-f(a)]/h is 6h+12a-2 in the function f(x)=4-2x+6[tex]x^{2}[/tex].

Given a function f(x)=4-2x+6[tex]x^{2}[/tex].

We are told to find out the value of f(a), f(a+h) and [f(a+h)-f(a)]/hwhere h≠0.

Function is like a relationship between two or more variables expressed in equal to form.The value which we entered in the function is known as domain and the value which we get after entering the values is known as codomain or range.

f(a)=4-2a+6[tex]a^{2}[/tex] (By just putting x=a).

f(a+h)==[tex]4-2(a+h)+6(a+h)^{2}[/tex]

=4-2a-2h+6([tex]a^{2} +h^{2} +2ah[/tex])

=4-2a-2h+6[tex]a^{2} +6h^{2} +12ah[/tex]

=[tex]6a^{2} +6h^{2}-2a-2h+12ah[/tex]

[f(a+h)-f(a)]/h=[[tex]6a^{2} +6h^{2}-2a-2h+12ah[/tex]-(4-2a+6[tex]a^{2}[/tex] )]/h

=[tex](6a^{2} +6h^{2} -2a-2h+12ah)/h[/tex]

=[tex](6h^{2} -2h+12ah)/h[/tex]

=6h+12a-2.

Hence the value of function f(a)=4-2a+6[tex]a^{2}[/tex], f(a+h) is [tex]6a^{2} +6h^{2} -2a-2h+12ah[/tex] , [f(a+h)-f(a)]/h is 6h+12a-2 in the function f(x)=4-2x+6[tex]x^{2}[/tex].

Learn more about function at https://brainly.com/question/10439235

#SPJ1